Vivencias de portadores con diabetes mellitus 2 - Bermudez Delfin, Diana Johanna (2010)
The present work of investigation of type Qualitative Fenomenológica, it has the intention of analyzing comprehensivamente the experiences that have the carriers of Diabetes Mellitus 2 concerning his disease; of the association "Elías Rodríguez" of Huamachuco's city. 14 major Adults took part in the study between the ages from 50 to 80 years of age, the information was obtained across the interview fenomenológica on the basis of the question norteadota which are the experiences that have the carriers of Diabetes Mellitus 2 concerning his disease?, I consider the aspects of the methodological path according to Martin Heidegger; as for the description and reduction fenomenológica as well as the vague and medium interpretation and the hermeneutic analysis. The sense ex--sistencial allows to understand that these patients live being in this daily in a luck of Learning To coexist with the Diabetes Mellitus 2 ". In the construction of the lived experiences develó in many occasions one thinks in a psychological crisis, that it demonstrates, intense suffering, deep sadness, weeping, pain, desperation, fault and especially it distresses for what could happen in the future. Likewise they demonstrate that to coexist with this disease is difficult and overwhelming for all the changes that they present day after day. Nevertheless opposite to this threatening situation, it arises as response to the need to believe in a top force that it will relieve and help in the fight with the disease for what they believe that God is with them taking care of them and supporting to be able to continue living, at par that feel the support of his family as a strength to continue forward.